PMO-221 Appropriateness of follow-up indications after colonic polyp removal: audit of current practice in a district general hospital. (28th May 2012) - Diss, J K J; Hashim, A; Arokianathan, D; Colquhoun, J; Tritto, G
Abstract : Introduction: Demand for colonoscopy is increasing worldwide due to the implementation of colon cancer screening programmes. According to current guidelines, the indication and timing for surveillance colonoscopy after removal of colonic adenomas are based on a risk estimation taking into account number and size of adenomas removed. In this study we audited the compliance with guidelines in the current practice of two district general hospital endoscopy services. Methods: The study was conducted at the King George and Queen's Hospitals in Essex (UK). All colonoscopies from June to August 2011 were retrospectively reviewed. All polyp-finding colonoscopies were selected and relevant data were retrieved from electronic records, patient notes and histopathology reports. The appropriate follow-up indication was established according to current British Society of Gastroenterology (BSG) guidelines, taking into account previous risk status, number and size of colonic adenomas. Finally the ideal indication was compared with the actual follow-up indication given to each patient. Results: A total of 1438 colonoscopies were reviewed. Polyps were found and removed in 314 (22%). Only 205 were included in further analysis. The remaining 109 were excluded because further follow-up indication was based on different issues (12 IBD, 19 colon cancers, 34 technical problems, 21 unknown previous risk status, 23 referred for surgery). Of the included 205, 34 patients were given an appointment in 1 year (high risk), one in 2 years, 28 in 3 years (intermediate risk), 142 in 5 years or no follow-up (low risk). The follow-up indication was compliant with BSG guidelines in 136 (66.3%) cases. In 33 (16.1%) patients the follow-up appointment was scheduled too early and in 4 (2%) too late. The remaining 32 (15.6%) were booked for later decision in outpatient clinic. They belonged to the intermediate (No.=28) and high (No.=4) risk groups. Overall, in the 3-months period, 24 inappropriate colonoscopies and 32 extra outpatient appointments were scheduled for the following year alone. In a further step we reviewed 154 histopathology results of benign polyps and found that 22 (14.3%) more patients could have had their follow-up appointment modified on the basis of the final histopathology finding (2 earlier and 20 later). Conclusion: The overall compliance with BSG guidelines in the evaluated period was 66.3% which is higher to that reported in previous studies. Nevertheless in only 3 months a significant inappropriate workload for endoscopy and outpatient clinics was generated. A more careful compliance with guidelines and a review of histopathology results could save a significant number of unnecessary colonoscopies and outpatient appointments. Competing interests: None declared.